PEMAHAMAN PETANI DALAM MENERAPKAN PRINSIP 5-C KAITANNYA DENGAN PENGEMBALIAN KREDIT BIDANG AGRIBISNIS - Djoni, Djoni; Rohman, Maman (University of Merdeka Malang, 2010)
The research aimed to find out the farmers understanding of the 5-C principlesapplication and of the credit payback in agricultural sector and its relationship. The methodused was a survey method toward the consumer of BRI Unit Neglasari Kecamatan SalawuKabupaten Tasikmalaya. The research location was purposively chosen considering that thelocation was the center of wood agroindustry wherein the largest capital aid was given. Therespondents were 21 people. The research was carried out from August to November 2008.The data collected was primary and secondary data. The primary data was tabulized andanalyzed descriptively, and the relationship between the two variables was analyzed usingnon-parametric statistical test. The hypothesis was tested using the Rank Spearmans Correla-tion Test. The results showed that the level of the farmers understanding of the 5-C prin-ciples application, i.e. character, capacity, capital, condition of economy, and collateral, wasclassified medium. 13 people were classified medium and 8 people were classified high.There was relation between the level of people understanding of the 5-C principles applica-tion and the credit payback of the wood agroindustry. The result indicated that the higherthe level of farmers understanding of the 5-C principles application was, the higher thecredit payback of the wood agroindustry would be.